Self Assessment Memory Scale (SAMS), a new simple method for evaluating memory function - Kowa, Hisatomo; Uchimura, Maki; Ohashi, Asuka; Hiroe, Mamoru; Ono, Rei (Frontiers in Aging Neuroscience, 2022)
We have developed a new method for easy self-assessment of changes in memory recall impairment, which can be used during very early stages of dementia. An 8-picture recall and a 16-word regression were assessed, respectively, and the index was calculated by adding up the ratio of correct responses to both tests. 85 subjects included 12 MCI, 8 AD, and 65 older persons with normal cognitive function were evaluated, and the correlation with the WMSR Logical Memory II score was examined. The results showed that there was a statistically signiﬁcant correlation between the 8-picture recall (R=0.872, p<0.0001) and the index (R=0.857, p<0.0001) respectively with the Logical Memory score. We have named this index as Self Assessment Memory Scale (SAMS), and are now developing a digital tool to enable easy and self-administered evaluation of recall.